Heat Denaturation Profiles of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) and Rubisco Activase and the Inability of Rubisco Activase to Restore Activity of Heat-Denatured Rubisco. - Eckardt, N. A. (1997)
We compared the heat-denaturation profiles of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and Rubisco activase and further examined the ability of Rubisco activase to restore the activity of heat-denatured Rubisco originally reported (E. Sanchez de Jimenez, L. Medrano, and E. Martinez-Barajas [1995] Biochemistry 34: 2826-2831). Rubisco was heat-treated in both the carbamylated and uncarbamylated forms and in the presence and absence of 10 mM dithiothreitol (DTT). Both forms were highly resistant to heat denaturation and further protection was gained in the presence of DTT. A 50% loss in total activity occurred after 1 h at 57.5 and 55.2[deg]C for uncarbamylated Rubisco and at 60.2 and 59.6[deg]C for carbamylated Rubisco, in each case with and without DTT, respectively. In contrast, Rubisco activase lost 50% activity after only 5 min at 33[deg]C and the loss in activity was not affected by the presence of Rubisco. When Rubisco, heat-denatured to various extents, was incubated at room temperature with Rubisco activase or bovine serum albumin as a control, Rubisco activase did not have a significant specific ability to restore Rubisco activity. We conclude that Rubisco activase alone does not have the ability to restore the activity of heat-denatured Rubisco and is unlikely to protect or restore Rubisco activity from heat denaturation in vivo because it is more heat-labile than Rubisco.